Antiepileptic Drug Use and the Risk of Stroke Among Community‐Dwelling People With Alzheimer Disease: A Matched Cohort Study. Issue 18 (18th September 2018) - Sarycheva, Tatyana; Lavikainen, Piia; Taipale, Heidi; Tiihonen, Jari; Tanskanen, Antti; Hartikainen, Sirpa; Tolppanen, Anna‐Maija
Abstract : Background: People with Alzheimer disease (AD) are more predisposed to seizures than older people in general, and use of antiepileptic drugs (AEDs) is more frequent. AED use has been linked to a higher risk of vascular events in the general population; however, it is not evident whether the same risk exists in people with AD. We assessed the risk of stroke associated with incident AED use among people with AD. Methods and Results: The MEDALZ (Medication Use and Alzheimer's Disease) cohort includes all Finnish people who received a clinically verified AD diagnosis (N=70718) from 2005 to 2011. People with previous strokes were excluded. For each incident AED user (n=5617) one nonuser was matched according to sex, age, and time since AD diagnosis. Analyses were conducted with Cox proportional hazards models and inverse probability of treatment weighting. Compared with nonuse, AED use was associated with an increased risk of stroke (inverse probability of treatment weighting hazard ratio (HR), 1.37; 95% confidence interval [CI], 1.07–1.74). The risk was strongest during the first 90 days (adjusted HR, 2.36; 95% CI, 1.25–4.47) of AED use. According to stroke type, the association was with ischemic strokes (inverse probability of treatment weighting HR, 1.34; 95% CI, 1.00–1.79) and hemorrhagic ones (inverse probability of treatment weighting HR, 1.44; 95% CI, 0.86–2.43). The stroke risk of users of older AEDs did not differ from that of the users of newer AEDs (adjusted HR, 1.04; 95% CI, 0.71–1.53). Conclusions: AED use was related to an increased risk of stroke, regardless of AED type. Our results highlight caution in AED use in this vulnerable population.